Youth participation in village development (Study in Muara Badak Ulu Village, Kutai Kartanegara, East Kalimantan) - Trisna Waty Riza Eryani; Zaid; Rachma Sagita; Peni Astuti (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
The battle of earlier generations to realize the nation's aspirations is being carried on by youth. Youth are regarded as a group of individuals who are creative and have fresh perspectives on progress. Including youth in development requires giving them the chance to realize their diverse aspirations and aspirations. For the younger generation to be interested in development, this is a significant capital. This study seeks to understand the elements that affect young engagement in development in Muara Badak Ulu Village, Muara Badak District, and Kutai Kartanegara Regency. The research design is descriptive qualitative research with Milles and Huberman's data analysis model, which includes data collection, data reduction, data presentation, and conclusion drafting. The findings indicated that youth involvement in the building of a road divider in front of the elementary school and market, repair of the road bridge on RT. 14, and fogging in Muara Badak Ulu Village, both in terms of contributions of ideas and materials and assistance during the planning, implementation, and evaluation, is adequate. Young people's willingness, aptitude, and chance to participate in the development of Muara Badak Ulu Village are three characteristics that are starting to become apparent.